Visitors’ satisfaction towards tourism facilities at Tusan Beach, Miri - Eneng, Mohamad Dzulkhairi (2018)
Tusan Beach was rarely known to visitors or even locals. It began to be a popular beach after the ‘Blue Tears’ phenomenon was found and become viral through social media. To cope with the recent beach popularity, the two neighboring villages work together to provide basic facilities at the beach. As the beach is still undergoing development, authorities and management are unsure of visitors’ satisfaction with the beach tourism facilities. Therefore, this study evaluates the level of visitors’ satisfaction on tourism facilities at the beach. A total of 221 questionnaire was distributed to visitors between January and February 2018. Satisfaction levels of visitors towards tourism facilities were measured using the 5-point Likert Scale. Socio-demographic of visitors were also identified. Overall, visitors were moderately satisfied with the tourism facilities provided at Tusan Beach (M = 3.45). The attribute ‘visitors will promote the beach to others’ earned the highest mean (M = 3.97) while adequate parking areas obtained the lowest mean (M = 2.86). Multiple regression analysis results show five significantly influence factors towards the overall visitors’ satisfaction which are, visitors’ revisiting (t = 2.315, p = 0.022), monthly income (t = 2.169, p = 0.031), religion (t = 1.722, p = 0.087), education level (t =1.746, p = 0.083) and visitors’ accompaniment (t = -1.752, p = 0.081).